2014
DOI: 10.1016/j.drugalcdep.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the relationship between trait mindfulness and substance use behaviors

Abstract: Background The relationship between trait mindfulness and substance use behaviors has been inconsistent across studies. The current study is a meta-analysis aimed at quantifying the magnitude of this relationship, and at determining how this relationship varies in context of (1) mindfulness facets, (2) substance type, (3) sample characteristics, and (4) substance use severity. Methods A literature search was conducted using electronic databases. The literature search yielded 303 articles, but only 39 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 66 publications
11
76
0
11
Order By: Relevance
“…These findings are consistent with findings from previous work with college students (Bramm et al, 2013; Christopher et al, 2012) and findings from a recent meta-analysis (Karyadi et al, 2014), but inconsistent with other work that has linked trait mindfulness to other aspects of alcohol use behaviors (Eisenlohr-Moul et al, 2012; Leigh and Neighbors, 2009) and that has failed to find a relationship (Brooks et al, 2012; Garland et al, 2012; Shorey et al, 2014). Importantly, the current study suggests that collapsing across different trait mindfulness facets might explain inconsistencies across these studies (Smith et al, 2003).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings are consistent with findings from previous work with college students (Bramm et al, 2013; Christopher et al, 2012) and findings from a recent meta-analysis (Karyadi et al, 2014), but inconsistent with other work that has linked trait mindfulness to other aspects of alcohol use behaviors (Eisenlohr-Moul et al, 2012; Leigh and Neighbors, 2009) and that has failed to find a relationship (Brooks et al, 2012; Garland et al, 2012; Shorey et al, 2014). Importantly, the current study suggests that collapsing across different trait mindfulness facets might explain inconsistencies across these studies (Smith et al, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Using this conceptualization, a meta-analysis of 39 studies and found that the trait mindfulness-substance use behaviors relationship differs across specific trait mindfulness facets and substance use behaviors: (1) only acting with awareness, non-judgment, and non-reactivity are negatively associated with substance use behaviors; and (2) trait mindfulness is more strongly related with problematic substance use behaviors as compared to non-problematic substance use behaviors (Karyadi et al, 2014). However, this meta-analysis did not examine trait mindfulness and its facets in relation to separate alcohol use behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity measures were assigned to separate impulsivity traits based on a factor analysis by Whiteside and Lynam (2001) and by previous meta-analyses (Coskunpinar et al, 2013;Dir et al, 2014;Karyadi et al, 2014;Supplemental Table 1). Marijuana-related behaviors we assigned were based on current conceptualizations of marijuana use (e.g., lifetime use, current use, frequency of use; Martin et al, 2002;Felton et al, 2015; and negative marijuana consequences (e.g., dependence, marijuana-related problems; Hendershot et al, 2011;Stautz and Cooper, 2015;Ames et al, 2005).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Although the results from human studies neither support nor refute the neuroprotective benefits of environmental enrichment, research has recently become focused on developing cognitive training, such as working memory and mindfulness exercises, for attenuating and/ or preventing neuroplastic changes associated with these disorders (Rogers, Ferrari, Mosely, Lang, & Brennan, 2017;Ruffault et al, 2016;Chiesa & Serretti, 2014;Karyadi, VanderVeen, & Cyders, 2014;Lee, An, Levin, & Twohig, 2015;Tang, Tang, & Posner, 2016;Bega, GonzalezLatapi, Zadikoff, & Simuni, 2014;Corbett, Jeffers, Nguemeni, GomezSmith, & Livingston-Thomas, 2015;Milgram, Siwak-Tapp, Araujo, & Head, 2006;Zigmond & Smeyne, 2014).…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 99%